The Effect of Creativity and Product Innovation on Business Success in Coconut Shell Waste Craftsmen in The Bukit Lawang Plantation Village Bahorok District Langkat Regency - Elisa Fitri; Hesti Sabrina; Wan Rizca Amelia (Universitas Medan Area, 2022)
This study aims to determine